(untitled) (Global Journal of Management and Business Research, 2017)
The essence of this study was basically to examine objectively the lethargic nature of Public (government) expenditure leading to slow economic development in Nigeria. An ex-post facto research was carried out to ascertain the nature of Nigerian economic development, using judgmental sampling technique from the period 1970 -2014. We utilized data on government capital expenditure, and recurrent expenditure sourced from CBN. Our data collection instrument for this study was the non-probabilistic sampling technique. We hypothesize and analyse our data using t-test, F-test and other statistical tools using the variables of Government Recurrent expenditure (GREX), and Government Capital Expenditure (GCEX) as indicators of economic development.